2020
DOI: 10.1186/s12913-020-05499-6
|View full text |Cite
|
Sign up to set email alerts
|

Geographic availability to optometry services across Canada: mapping distribution, need and self-reported use

Abstract: Background: This research investigates the distribution of optometrists in Canada relative to population health needs and self-reported use of vision services. Methods: Optometrist locations were gathered from provincial regulatory bodies. Optometrist-to-population ratios (i.e. the number of providers per 10,000 people at the health region level) were then calculated. Utilization of vision care services was extracted from the Canadian Community Health Survey (CCHS) 2013-2014 question regarding self-reported co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Therefore, the financial barrier prevents low‐vision patients from accessing the services offered by these private practices, leading to a lower likelihood of optometrists providing low‐vision services. While financial constraints are a significant factor, other barriers such as lack of space and inadequate training may also contribute to the limited provision of low‐vision services by optometrists in T&T. Similar findings were reported in studies conducted in Ghana 5,21,22 …”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the financial barrier prevents low‐vision patients from accessing the services offered by these private practices, leading to a lower likelihood of optometrists providing low‐vision services. While financial constraints are a significant factor, other barriers such as lack of space and inadequate training may also contribute to the limited provision of low‐vision services by optometrists in T&T. Similar findings were reported in studies conducted in Ghana 5,21,22 …”
Section: Discussionsupporting
confidence: 82%
“…Differences in access to other primary care services have also been identified between urban and rural regions in Canada, with lower accessibility for residents of rural communities, consistent with our findings. 24 - 26 Most related to our work, research by Sibley and Weiner 24 reported that the lowest influenza vaccination rates were observed among the most rural Canadians, and a recent report by Environics Analytics found higher rates of COVID-19 vaccination hesitancy among rural populations. 27 Furthermore, as indicated in Table 2 and Appendix 2 , our analysis has found that a number of communities do not have access to pharmacists in their Census Subdivision at all, as evidenced by communities that would continue to have no or below-threshold availability even if all pharmacists practising in that region were authorized to administer injections.…”
Section: Discussionmentioning
confidence: 56%
“…Eye care distribution to the use of vision care services in relation to population needs was compared by cross-classification mapping. According to this spatial analytic study, the nationwide distribution of eye care services is variable across Canada and predominantly concentrated in cities ( 26 ). Even though generalization of the findings should be cautious with data quality on health service location, utilization status, and potential geographical factors, these spatial epidemic outcomes offer a better understanding and evaluation of accessed health care resources and help policy-makers, and care providers to consider facilitating the use of eye care services at national, provincial, and health region levels.…”
Section: Application In Ophthalmologymentioning
confidence: 99%